Clinical, echocardiographic and angiographic correlation of acute coronary syndrome in women at a tertiary care centre - Krishnegowda, Chetana; Swamy, Mallikarjuna H. (International Journal of Research in Medical Sciences, 2017)
Background: The evaluation of coronary artery disease (CAD) in women presents a unique and difficult challenge for clinicians, owing to the differences in symptoms, clinical features and mortality as compared to men. This study is to analyze the risk factors, clinical presentation, complications and outcome in women who presented with myocardial infarction. Methods: The study was conducted among women admitted with acute myocardial infarction in coronary care unit of KIMS Hospital, Hubli from January 2013 to December 2013. After inclusion and exclusion criteria 100 women underwent detailed history, clinical examination and investigations. Results: The mean age of the study group was 57.98 years. 49% of patients presented with atypical symptoms with majority being postmenopausal (87%). HDL cholesterol was the commonest risk factor followed by HsCRP, increased waist circumference and diabetes mellitus, with the least common risk factor being elevated homocysteine. Pump failure was the commonest complication. Double vessel disease was more common in diabetic population whereas single disease was common in non-diabetic population. Conclusions: Women clinically present with atypical symptoms that resulted in significant delay to reach hospital. Novel risk factors like HsCRP and homocysteine may improve risk detection in women with CAD. Identifying and targetting lifestyle risk factors. Diabetes mellitus in particular is the key to reduction in CAD in women.